Alpha1-Adrenergic Receptor Mediated Long-Term Depression at CA3-CA1 Synapses Can Be Induced via Accumulation of Endogenous Norepinephrine and Is Preserved Following Noradrenergic Denervation - Dyer-Reaves, Katie; Goodman, Anthoni M.; Nelson, Amy R.; McMahon, Lori L. (Frontiers in Synaptic Neuroscience, 2019)
Locus coeruleus (LC) provides the sole source of noradrenergic (NA) innervation to hippocampus, and it undergoes significant degeneration early in Alzheimer’s disease (AD). Norepinephrine (NE) modulates synaptic transmission and plasticity at hippocampal synapses which likely contributes to hippocampus-dependent learning and memory. We previously reported that pharmacological activation of α1 adrenergic receptors (α1ARs) induces long-term depression (LTD) at CA3-CA1 synapses. Here, we investigated whether accumulation of endogenous NE via pharmacological blockade of norepinephrine transporters (NETs) and the NE degradative enzyme, monoamine oxidase (MAO), can induce α1AR LTD, as these inhibitors are used clinically. Further, we sought to determine how degeneration of hippocampal NA innervation, as occurs in AD, impacts α1AR function and α1AR LTD. Bath application of NET and MAO inhibitors in slices from control rats reliably induced α1AR LTD when β adrenergic receptors were inhibited. To induce degeneration of LC-NA innervation, rats were treated with the specific NA neurotoxin DSP-4 and recordings performed 1–3 weeks later when NA axon degeneration had stabilized. Even with 85% loss of hippocampal NA innervation, α1AR LTD was successfully induced using either the α1AR agonist phenylephrine or the combined NET and MAO inhibitors, and importantly, the LTD magnitude was not different from saline-treated control. These data suggest that despite significant decreases in NA input to hippocampus, the mechanisms necessary for the induction of α1AR LTD remain functional. Furthermore, we posit that α1AR activation could be a viable therapeutic target for pharmacological intervention in AD and other diseases involving malfunctions of NA neurotransmission.